Multifunctional Silicon–Carbon Nanohybrids Simultaneously Featuring Bright Fluorescence, High Antibacterial and Wound Healing Activity. Issue 9 (25th January 2019) - Hu, Guyue; Song, Bin; Jiang, Airui; Chu, Binbin; Shen, Xiaobin; Tang, Jiali; Su, Yuanyuan; He, Yao
Abstract: In this work, a class of multifunctional silicon–carbon nanohybrids (designated as SiCNs), which simultaneously possess aqueous dispersibility, bright fluorescence (photoluminescence quantum yield [PLQY]: ≈28%), as well as high antibacterial and wound healing activity, is presented. Taking advantage of these unique merits, cell distribution and pharmacological behavior of the SiCNs is first investigated through tracking their strong and stable fluorescence. The high bacteria inhibition ability (≈82.9% killing rate toward S. aureus) and hemostatic effects (shorten the bleeding time from ≈60 to ≈15 s) of the resultant SiCNs are then demonstrated. Moreover, the wound closure promotion activity (10% lead in wound contraction) is systematically demonstrated in vivo, which is especially suitable for wound healing applications. The results suggest the SiCNs as a new kind of high‐performance multifunctional nanoagents suitable for various biological and biomedical utilizations. Abstract : Herein, an "organic–inorganic hybridization" strategy is proposed to enhance the bioavailability of herbal medicine via integration with silicon nanosystems. The obtained silicon–carbon nanohybrids (SiCNs) possess bright fluorescence for bioimaging analysis. Of particular note, the SiCNs feature high medicinal effectiveness in various wound healing applications, which can promote hemostasis, combat bacterial infection, and expedite wound closure process simultaneously.